IMPROVING THE STUDENTS WRITING DESCRIPTIVE TEXT BY USING PICTURES MEDIA IN SENIOR HIGH SCHOOL AT THE TENTH GRADE OF MA SWASTA IKHLASIYAH GUPPI MUSLIMIN - Ridwin Purba; Nurmasdiah Naibaho (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2021)
The research focused of Improving Students Writing Descriptive Text by Using Picture Media in senior high school of MA Swasta Ikhlasiyah Guppi Muslimin Academic year 2020/2021. The research design was quantitative method. The population was 29 students and the sample was taken by Sugiyono 2017: 81 at class X with 29 students. The instrument was easy test. The data analysis started from scoring composition and finding different mean of the score. Based on the data analysis the researcher finding also proved that in the pre-test students mean score was only 1475 and the mean was 50,86 and after the treatment, it had been improved since the post-test data was 2168 and the mean was 74,75. After analyzing the data, it was concluded that the use of picture media gives significant contribution in improving student’s competence in writing descriptive text at grade X MAS Ikhlasiyah Guppi Muslimin in academic year 2020/2021